2010
DOI: 10.4300/jgme-d-10-00105.1
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Residents Through Multiple Residency Programs: A Different Approach for Measuring Residents' Rates of Continuing Graduate Medical Education in ACGME-Accredited Programs

Abstract: Background Increased focus on the number and type of physicians delivering health care in the United States necessitates a better understanding of changes in graduate medical education (GME). Data collected by the Accreditation Council for Graduate Medical Education (ACGME) allow longitudinal tracking of residents, revealing the number and type of residents who continue GME following completion of an initial residency. We examined trends in the percent of graduates pursuing additional clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…An earlier study of Accreditation Council for Graduate Medical Education-accredited GME programs reported that the proportion of US medical school graduates who continued in GME after completing requisite training for initial board certification differed substantially by specialty. In that study, across all specialties examined, 31.6% of US medical graduates overall continued in GME after completing initial specialty training, but there were striking differences between specialties—only 7.5% of trainees who completed initial specialty training in family medicine continued in GME, whereas 60.9% of those who completed initial specialty training in IM did so 57. Further research is warranted to examine the relationship between subspecialty training and receipt of federal research grants.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…An earlier study of Accreditation Council for Graduate Medical Education-accredited GME programs reported that the proportion of US medical school graduates who continued in GME after completing requisite training for initial board certification differed substantially by specialty. In that study, across all specialties examined, 31.6% of US medical graduates overall continued in GME after completing initial specialty training, but there were striking differences between specialties—only 7.5% of trainees who completed initial specialty training in family medicine continued in GME, whereas 60.9% of those who completed initial specialty training in IM did so 57. Further research is warranted to examine the relationship between subspecialty training and receipt of federal research grants.…”
Section: Discussionmentioning
confidence: 85%
“…In that study, across all specialties examined, 31.6% of U.S. medical graduates overall continued in GME after completing initial specialty training; but there were striking differences between specialties—only 7.5% of trainees who completed initial specialty training in family medicine continued in GME, whereas 60.9% of those who completed initial specialty training in IM did so. (57) Further research is warranted to examine the relationship between subspecialty training and receipt of federal research grants.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with recent findings for obstetric graduates, as well as in the ACGME research that tracked residents in multiple specialties and programs. 8,9 Additional information from the Databook (not shown) suggests that the modest increase in the number of residents entering the pipeline is due to 2 factors: (1) some growth in primary care programs, primarily in 2012, resulting from the Health Resources and Services Administration's Teaching Health Center Graduate Medical Education funding program; 10 and (2) Number of Residents Entering Pipeline and Continuing GME Programs, by Academic Year Abbreviation: GME, graduate medical education.…”
Section: Resultsmentioning
confidence: 99%
“…A lo largo de estos años de implementación, durante los cuales ya existe más de una generación de posgrados que han logrado su título de ginecotocólogos con formación en el interior del país, creemos que se ha demostrado a partir de las evaluaciones de los posgrados, pero sobre todo del logro del objetivo final que es el título de la especialidad, que la formación es posible en los diferentes CEDA, con dispositivos docentes innovadores. Si bien no es un punto que hayamos evaluado, sabemos que los profesionales médicos entrenados en centros de alta complejidad tienen más experiencia en el cuidado de ciertos casos que en los más prevalentes y simples (10) . Seguramente de acuerdo con las características asistenciales diferentes del CHPR, centro de referencia nacional de gineco-obstetricia, este cambio en la distribución de los escenarios asistenciales de aprendizaje impacte sobre la integralidad del abordaje de la especialidad.…”
Section: Figura 3 Promedio De Procedimientosunclassified